A novel combustion fuel for the synthesis of nanocrystalline ZnAl2O4 particles based on the thermodynamic correlations and their structural and optical studies. Issue 3 (1st February 2022) - Srinatha, N.; Rudresh Kumar, K.J.; Suresh Kumar, M.R.; Madhu, A.; Angadi, Basavaraj
Abstract: ZnAl2 O4 nanocrystalline particles were prepared using the solution combustion method using a new combustion fuel, Leucine. The prepared samples' structural, microstructural–elemental composition, and optical characteristics were investigated using XRD, SEM-EDS, and UV–Visible spectroscopy. As-synthesized ZnAl2 O4 nanoparticles are polycrystalline, with no secondary phases, and crystallized in a cubic - spinel structure. The polycrystalline nature of the prepared sample is due to the exothermicity of fuel and oxidizer, which demonstrate that the fuel utilized (Leucine) provided adequate energy for the production of nanoparticles in their as-synthesized form, as supported by adiabatic temperature through thermodynamic calculations. The thermodynamic calculations also include a universal method to estimate the specific heat capacity at constant pressure. Furthermore, even after 2 h of calcination at 600 °C, ZnAl2 O4 exhibits a single phase with no secondary phases, indicating the material stability and single-phase nature. The crystallinity of ZnAl2 O4 nanoparticles was observed to increase with increasing annealing temperature. SEM micrographs of as-synthesized samples exhibit the formation of dense particles, voids, and pores in the as-synthesized sample. In addition, tiny aggregates were detected on the surface of more prominent clusters, which reduced as the calcination progressed. In addition, calcined samples exhibit a greater optical reflectance than as-synthesized samples. Tauc's graphs were used to compute the optical energy bandgap. The calculated energy band gap is redshifted to that of the bulk material. The bandgap energy decreases upon calcination, suggesting that the prepared materials have a larger crystallite size or more crystallinity. Correlations were found between the Tad, and the structural and optical properties of the prepared samples. The findings suggest that Leucine could be used as a novel combustion fuel to produce crystalline ZnAl2 O4 nanoparticles in their as-synthesis form.